Foreclosure of landed-properties in Kelantan with reference to the Kelantan Malay reservation enactment / Abdul Hadi Awang Hamat - Awang Hamat, Abdul Hadi (1994)
Foreclosure of landed properties in Kelantan has become more prominent of late due to the inability of chargors to meet the conditions stipulated in the charge. This dissertation shall highlight the problems faced by chargees in Kelantan in recovering collaterals pledged by chargors and would endeavour to explain how this situation has come about. To understand this complex problem we have to examine the relevant factors influencing land dealings in Kelantan. Amongst the most prominent is the Kelantan Malay Reservation Enactment 1930 which has been styled under the Federated Malay States Malay Reservation Enactment 1913. We shall explain why the Enactment was enacted and it's effect on land dealings in Kelantan. We shall also explain the relevant requirements of the National Land Code 1965 pertaining to foreclosure and the procedures adopted by the land office and High Court in auction proceedings.